2006
DOI: 10.1086/505713
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus C (GBV‐C) Infection in Hepatitis C Virus (HCV)/HIV–Coinfected Patients Receiving HCV Treatment: Importance of the GBV‐C Genotype

Abstract: GBV-C coinfection was extremely common. GBV-C RNA clearance with HCV therapy was associated with neither short-term loss of HIV control nor impaired immune status. The association of GBV-C genotype 2 with higher CD4(+) cell counts merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 52 publications
13
56
1
Order By: Relevance
“…We observed a significant difference in CD4 cell counts in HIV-positive persons co-infected with GBV-C genotype 2 compared to GBV-C genotype 1 even after controlling for race, HIV viral load and ART use (Schwarze-Zander et al, 2006). GBV-C genotype 2 was also marginally more sensitive to interferonbased HCV therapy than genotype 1.…”
Section: Consensusmentioning
confidence: 71%
See 1 more Smart Citation
“…We observed a significant difference in CD4 cell counts in HIV-positive persons co-infected with GBV-C genotype 2 compared to GBV-C genotype 1 even after controlling for race, HIV viral load and ART use (Schwarze-Zander et al, 2006). GBV-C genotype 2 was also marginally more sensitive to interferonbased HCV therapy than genotype 1.…”
Section: Consensusmentioning
confidence: 71%
“…However, some other studies have not shown such a survival advantage (Birk et al, 2002;Björkman et al, 2004). While it has been suggested that GBV-C genotype may play a role in modulating HIV disease progression (Alcalde et al, 2010;Muerhoff et al, 2003;Schwarze-Zander et al, 2006), which could explain the divergent findings among these studies, additional investigation is required to evaluate this hypothesis adequately. As a necessary first step, we characterized complete ORF sequences from individuals with GBV-C infection in the United States.…”
mentioning
confidence: 99%
“…However, anti-E2 antibodies are occasionally found during active viraemia and some of these individuals may be in the act of clearing viraemia (Schwarze-Zander et al, 2006;Tan et al, 1999;Williams et al, 2004). Some recent reports describe the detection of anti-HPgV peptide antibodies (Fernández et al, 2013;Gó mara et al, 2011); however, no clear relationship between peptide-reactive antibodies in actively HPgV-infected or convalescent subjects has been reported.…”
Section: B-cell Function and Antibody Productionmentioning
confidence: 99%
“…Several lines of evidence suggest a possible inhibition of HIV-1 by GBV-C through increase in soluble ligands for HIV-1 correceptor and activation of innate immunity (Lalle, 2008;Mohr & Stapleton, 2009). In addition, the beneficial effect of GBV-C on survival of HIV-1 infected patients might be genotype specific (Schwarze-Zander et al, 2006). Two GBV-C proteins, E2 and NS5A, have been shown to modulate CD4+ T-lymphocyte chemokine receptor expression and chemokine release in vitro, then inhbiting HIV replication.…”
Section: Hiv Co-infectionmentioning
confidence: 99%